Nonlinearity of runoff response to global mean temperature change over major global river basins - Zhang, X; Tang, Q; Liu, X; Leng, G; Di, C (American Geophysical Union, 2018)
We investigated the nonlinearity of runoff response to global mean temperature (GMT) change in the CMIP5 climate models at the river basin scale globally. Results show that changes in long‐term mean annual runoff are nonlinear with GMT rise over most extended sub‐tropical basins, suggesting that estimation of future runoff change derived from the linear scaling relations would be biased. As for the inter‐annual variability, nonlinearities are apparent mainly in Central and Western Asia, Southern and Western Africa, most of Europe and Australia when GMT increases beyond 1.5°C. This suggests that impacts of climate change under 1.5°C GMT rise on runoff variability should not be simply scaled from that under a 2°C warming world. Our results highlight the contrasting response of areal runoff to GMT rise across global major river basins, and reveal the threshold of GMT increment at which the nonlinear runoff response is projected to emerge.